Analysis of the Influence of Online Transportation Application Usage Using the EUCS Model in Measuring User Satisfaction in Bandung City: Case Study: InDrive Users - Akbar, Imannudin; Anggraeni, Hilma; Habibi, Chairul; Nugraha, Arif Bakti (LPPM STMIK Mardira Indonesia, 2024)
The swift advancement of technology has profoundly influenced the transportation industry, especially in digital transportation services. InDrive provides a Peer-to-Peer transportation service for passengers, wherein travel conditions are established through agreements between passengers and drivers. This study seeks to assess user happiness with the InDrive application in Bandung utilizing the End User Computing Happiness (EUCS) model. A quantitative methodology was utilized to gather data via online questionnaires from a sample of 201 active InDrive customers in Bandung who have utilized online transportation services. The hypotheses were tested using SEM-PLS analysis with SmartPLS 3.0 software. The findings indicate that four factors—content, Accuracy, Ease of Use, and Timeliness—positively and significantly affect user satisfaction. One of the five proposed hypotheses was rejected: the Format variable had no significant impact on user satisfaction, evidenced by a t-statistic of 0.701, below the t-table value of 1.972, and a p-value of 0.484, surpassing the significance threshold of 0.05. This research highlights the necessity to improve the aspects that influence user happiness. Enhancing Content, Accuracy, Usability, and Timeliness will enable InDrive to improve service quality and user experience. The minimal influence of the Format variable indicates a necessity for additional research, offering critical insights for players in the online transportation industry to enhance their services and align more closely with user expectations.